Integrating field service management and product policy with corporate strategy : a systematic approach - Mathe, H. (Cranfield University, 1988)
This research is concerned with the development and implementing of an integrated management system appropriate for use within the field service activities of an industrial firm. Field service or after-sale service management system is viewed as an integrated process which includes several service producing subsystems. The purpose of their interacting is to achieve a given level of operational availability, as well as a relative adjust.:::-oent, throughout the products life cycle which improve the customer loyalty. The- growth and profitability of numerous companies tend to be progressively founded on the development of challenging service policies which go along with the commercialisation of tangible products. Even today, little has been written on the question of after-sales service, with the exception of some technical developments related to the reliability and maintenance of complex equipment's. Consequently, the first objective of this research consists in proposing a conceptual definition of service-mix associated, before and after the sales act, with the commercialization of tangible products. Having identified the management deficiencies existing in certain companies, both conceptual and technical, an integrated management system is theoritically developed which . overcomes theses deficiencies. Such a system is partly based on a product management approach, applied to the case of after sales. It is composed of four stages : 1. Formulation of the after sales strategy as being the expression of the company's prevailing mode of competition 2. Elaboration of the services programming antl information systems 3. Designing of the organisational structure 4. Identification of performance control tools well adapted to the after sales activity. The management model of the after-sales service function is viewed here as a set of mechanisms that integrate the offer "product service" furnished by an industrial firm. It is thus a process which concurs to a more efficient management of lone more or less conflicting interfaces existing between the different functions contributing to the design, production, distribution and support of the functionality required by the market.